Anesthesiological Support for Reconstructive Operations on the Aortic Arch: Nuances of Organoprotection - Rezvanovich, Salikhov Masud; Huseynovich, Satuev Yusup; Alievich, Aliev Shamil (International Journal of Psychosocial Rehabilitation, 2020)
This article considers the issues of anesthesia during operations on the aortic arch, and research on the topic under examination. It should be noted that operations on the aortic arch are one of the most complex surgical procedures.